Accounting Education: New Horizons for the Profession (Book). - Burns, Thomas J.; Wasley, Robert S. (The Accounting Review, 1978)
Abstract Reviews the book "Accounting Education: New Horizons for the Profession," edited by Donald H. Skadden.